(untitled) (Caligrama: Revista de Estudos Românicos, 2025)
This paper presents the manner in which FrameNet Brasil has developed annotation of pragmatic frames, with a focus on those evoked by interactive gestures used in turn organization during face-to-face conversation. As corpus, we chose the interviews shown in the episodes of the first season of the Brazilian television series Pedro Pelo Mundo. We used Webtool 4.0, the newest version of this tool, for annotation of a total of 47 interactive gestures. As a result, we were able to demonstrate that these interactive gestures evoke specific pragmatic frames – turn passing, turn confirmation and turn taking – and are tools which make conversation a multimodal means of communication. Our research shows that the annotation of pragmatic frames is not only possible, but also useful for pragmatic investigations and for expanding FrameNet multimodal analysis.